2009
DOI: 10.1144/0016-76492008-067
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic signals from Callovian–Kimmeridgian (Middle–Upper Jurassic) belemnites and bulk organic carbon, Staffin Bay, Isle of Skye, Scotland

Abstract: The stable isotope data presented here significantly extend and expand upon previous isotopic investigations of the Middle to Late Jurassic interval. The belemnite samples collected from the Staffin Bay and Staffin Shale formations from the Isle of Skye, Scotland, yielded oxygen isotope values consistent with Callovian-Kimmeridgian palaeotemperatures of 6.7-20.6 8C. The carbon isotope data comprise one of the first moderately high-resolution investigations of the relationship between terrestrial ä 13 C org (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 51 publications
9
28
0
2
Order By: Relevance
“…In this context, it was concluded that the Callovian-Oxfordian positive and the Middle Volgian negative 13 C org excursions and the Kimmeridgian-Middle Volgian negative trend for the investigated Middle Jurassic-Lower Cretaceous Agardhfjellet Formation are consistent with several other anomalies reported from elsewhere in the Boreal realm (e.g. Hammer et al, 2012;Katz et al, 2005;Nunn et al, 2009;Padden et al, 2002;Zakharov et al, 2014) and therefore reflect a global event.…”
supporting
confidence: 82%
“…In this context, it was concluded that the Callovian-Oxfordian positive and the Middle Volgian negative 13 C org excursions and the Kimmeridgian-Middle Volgian negative trend for the investigated Middle Jurassic-Lower Cretaceous Agardhfjellet Formation are consistent with several other anomalies reported from elsewhere in the Boreal realm (e.g. Hammer et al, 2012;Katz et al, 2005;Nunn et al, 2009;Padden et al, 2002;Zakharov et al, 2014) and therefore reflect a global event.…”
supporting
confidence: 82%
“…MS magnetic susceptibility carbonate carbon in the Tethyan realm and organic carbon in the Boreal realm. Boreal realm organic carbon records from age equivalent sections in the UK (Morgans-Bell et al 2001), Scotland (Nunn et al 2009) and Russia (Riboulleau et al 1998;Price and Rogov, 2009) show a conspicuous positive excursion in the R. cymodoce Zone (Sub-boreal equivalent to the S. platynota/A. hypselocyclum zones) and are correlated here to the Tojeira-1 section C-isotope record (Fig.…”
Section: Correlationsupporting
confidence: 52%
“…4). Likewise, from the Isle of Skye, Scotland, there is a peak in the C-isotope record in the R. cymodoce Zone (Nunn et al 2009), and in the carbonate carbon record for Makariev village, Russia, is a definitive positive peak (Riboulleau et al 1998;Price and Rogov, 2009). The cyclostratigraphical age suggestion for the Tojeira-1 section (constrained by biostratigraphy) places a conspicuous peak of similar scale to those Boreal records outlined, in the early A. hypselocyclum Zone.…”
Section: Correlationmentioning
confidence: 55%
See 1 more Smart Citation
“…Likewise a declining marine δ 13 C org trend is seen in DSDP site 534A data reported by Falkowski et al (2005) from the Tithonian, before a pronounced positive event is seen associated with the Valanginian (Patton et al, 1984). Those Late Jurassic and Early Cretaceous δ 13 C org data derived from woody material and charcoal (Nunn et al, 2009(Nunn et al, , 2010Pearce et al, 2005;Gröcke et al, 2005) also reveal a long-term decline in carbon-isotopes through the Late Jurassic and a positive Valanginian excursion closely matching the marine carbon-isotope curves. Notably a lack of data is apparent for the latest Tithonian and earliest Berriasian.…”
Section: Accepted M Manuscriptmentioning
confidence: 56%